Treatment of moderate to severe keratoconus with 6-mm Intacs SK - Niknam, Sasan (International Journal of Ophthalmology Press, 2012)
AIM: To evaluate the effect of Intacs SK corneal ring segment implant for treatment of patients with moderate to severe keratoconus, who have clear central cornea and cannot tolerate contact lens. METHODS: In this prospective, non-comparative, interventional case series study performed in Dena Hospital, Shiraz, Iran, thirty-seven eyes of thirty-six patients with moderate to severe keratoconus, clear central cornea, and contact lens intolerance were enrolled and underwent Intacs SK corneal ring segment implantation. Preoperatively, uncorrected distance visual acuity (UCDVA), best-corrected distance visual acuity (BCDVA), central corneal thickness(CCT) and average keratometry (Av-K) were measured and compared with post-operative results at one week, one month, three months, and six months. RESULTS: Mean preoperative UCDVA and BCDVA were (1.32±0.31)logMAR and (1.07±0.27)logMAR, respectively. Av-K was (52.13±0.39)D, and the CCT was (432±39.5)µm. Post-operative examinations showed a clinically significant improvement in both UCDVA and BCDVA (P<0.001). There was also a significant effect based on the time of assessment on both UCDVA and BCDVA and both parameters had a continuous improvement during the follow-up period. Three months after operation there was a statistical significant reduction of Av-K (P=0.0001), but there were no significant changes in CCT (P=0.149). CONCLUSION: Intacs SK corneal ring segment implants seem to be a safe and effective treatment option for patients who have keratoconus, clear central cornea, and contact lens intolerance.